2021
DOI: 10.1152/ajpheart.00300.2020
|View full text |Cite
|
Sign up to set email alerts
|

Altered calcium handling in cardiomyocytes from arginine-glycine amidinotransferase-knockout mice is rescued by creatine

Abstract: The creatine kinase system facilitates energy transfer between mitochondria and the major ATPases in the heart. Creatine-deficient mice, which lack arginine:glycine amidinotransferase (AGAT) to synthesize creatine and homoarginine, exhibit reduced cardiac contractility. We studied how the absence of a functional CK system influences calcium handling in isolated cardiomyocytes from AGAT knockouts and wild-type littermates as well as in AGAT knockout mice receiving lifelong creatine supplementation via the food.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(46 citation statements)
references
References 65 publications
2
43
1
Order By: Relevance
“…(2002), while the LTCC current–voltage relationship did not show a statistically significant difference between sexes, mean current density was larger in females than in males under control conditions, in agreement with our data (Laasmaa et al., 2021). LTCC current decay, found in our earlier work (Laasmaa et al., 2021), was faster in females than in males ( P = 0.04) under control conditions, with ISO reducing the decay similarly for both sexes (no statistically significant interactions between sex and ISO treatment when analysed by ANOVA). In other studies, no statistically significant difference in LTCC current decay was observed (Grandy & Howlett, 2006; Parks et al., 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…(2002), while the LTCC current–voltage relationship did not show a statistically significant difference between sexes, mean current density was larger in females than in males under control conditions, in agreement with our data (Laasmaa et al., 2021). LTCC current decay, found in our earlier work (Laasmaa et al., 2021), was faster in females than in males ( P = 0.04) under control conditions, with ISO reducing the decay similarly for both sexes (no statistically significant interactions between sex and ISO treatment when analysed by ANOVA). In other studies, no statistically significant difference in LTCC current decay was observed (Grandy & Howlett, 2006; Parks et al., 2014).…”
Section: Discussionsupporting
confidence: 92%
“…While we earlier did not find any statistically significant difference between sexes in L‐type calcium channel (LTCC) and sarco/endoplasmic reticulum Ca 2+ ‐ATPase (SERCA) expression (Laasmaa et al., 2021), we looked into the regulatory effect imposed by phospholamban, PLB and/or its phosphorylation on Ser16 (PKA phosphorylation) or Thr17 (CaMKII phosphorylation). We found that the expression of PLB and its phosphorylated forms was not statistically significantly different between sexes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Faller and co-workers have shown that impaired cardiac contractile function in Agat −/− mice is rescued by hArg, but not creatine (Faller et al, 2018). By contrast, Laasmaa et al showed that impaired calcium handling by isolated cardiomyocytes from Agat −/− mice is normalized by creatine supplementation when creatine is supplemented from weaning (Laasmaa et al, 2021). Taken together, these data suggest that hArg and creatine play differential roles in mediating the pathophysiological phenotypes of Agat −/− mice, which are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%